ASAL-USUL NAMA KAMPUNG BATTANGAN SUMENEP MADURA DALAM TINJAUAN STRUKTURALISME LEVISTRAUSS - Unggul Sudrajat; Khairul Umam (Jantra., 2018)
This descriptive-qualitative research looked at the toponym of Battangan village which is located under Sumenep Regency, Madura. The data were drawn from library research and interviews. The data were analysed using hermeneutic approach. The research result shows that the story about the origin of Batangan village reveals three identities of the local society which cannot be separated from the Madurese culture. The three identities are Islamic spirit, moral, and the characteristics of the local society.